Eksperimentalna analiza pogojev za kontrolo kakovosti montaže statorja elektromotorja z uporabo strojnega vida - Herakovič, Niko (Ventil (Ljubljana), 2007)
The industrial application of machine vision for quality control (QC) in the EM stator-assembly process is a multilayer problem that demands a great deal of expert knowledge, experience and innovation. Usually, the procedure for machine vision QC is split into a precise determination of the tasks and goals, machine-vision component selection and working conditions, component selection for the machine vision, and, finally, the development of an automatic part-handling system. This paper is focused on the determination of the machine-vision tasks and the influence of lighting on the inspection and measurement of the EM stator.
Keywords: kontrola kvalitete; montaža; osvetlitev; strojni vid